Isolation and Characterization of Bacteriophage T4 Base Plates - Poglazov, B. F. (1972)
A method for isolating bacteriophage T4 base plates from lysates of Escherichia coli B cells infected with the ts mutant in gene 19, ts B31 has been developed. By electrophoresis in polyacrylamide gel with sodium dodecyl sulfate the base plates have been shown to contain five to seven protein components with molecular weights of 36,000, 53,000, 66,000, 81,000, 87,000, and probably about 100,000. Electron microscope studies have demonstrated that base plates may occur in two structural states: in the form of hexagons or stars. Star rays and short fibrils are not radial or elongated and are turned sideways at an angle to the radius. Base plates do not complement in vitro with free tail cores isolated after disintegration of particles of the wild-type bacteriophage.